Colegialidade: experiências de Jorge Mario Bergoglio e sua influência no pontificado de Francisco - Silva, Mariane de Almeida (2018)
Pope Francis has been surprising the world since his arrival at the Vatican's most important balcony on March 13, 2013, when he was elected Supreme Pontiff of the Catholic Church. There, already in those brief minutes of his appearance, he draws attention by his gestures, by the way of his speaking, actig and mainly, by the way of being close to people. Still on that memorable day, Francis points to an way that, although not explicitly, becomes central in his ministry: Collegiality. This is noticeable at the moment when he calls himself bishop of Rome and calls the cardinals of brothers. Francis's words point to Collegiality. However, only a deeper inquiry is able to discover whether, in fact, Francis is a pope who lives the collegial spirit in his family and ministerial base. The present dissertation sought to know the theoretical and theological bases of Jorge Mario Bergoglio, the ecclesiological paths covered by him, regarding Collegiality. This work had, among other things, the intention of discovering if the experiences of Jorge Mario Bergoglio before the election contributed to the collegial tone present in the documents of Francis. For this, the research sought to show the roots of Collegiality present not only in the moment of the Second Vatican Council, but also the aspects of its reception in the different continents, particulary in Latin American soil, of which Bergoglio is a beloved son. It was too important to know the biographical-existential roots of the future archbishop of Buenos Aires. Recognizing such aspects of Bergoglio, it will be easier to discover who, in fact, is Francis and what his thoughts are for the Church and her mission